The importance of developing android-based Indonesian language dictionary for the blind (KABITUNA) - Azzhan Shahrul; Dwi Prastyo Nugroho (Politeknik Negeri Bali, 2017)
Indonesia is among the ranks of countries with the lowest literacy in the world. Precisely at rank 69 of 76 countries. If calculated the average Indonesian people only read one book per year. One of the reasons for the low literacy of Indonesia is the lack of understanding of Indonesian society with Indonesian vocabulary. Although Indonesian is an educational language which is also the national language and language of Indonesian unity, it can not be denied if Indonesian people do not fully master the Indonesian language. That's what causes the dictionary as a medium for discovering the meaning of words.On the other hand, until now Indonesia is not evenly able to facilitate the dictionary as a means of searching the meaning of words. Many Indonesian dictionaries only specialize for normal people only. Whereas the number of persons with disabilities in Indonesia reached 2.45% of the total population of Indonesia. Then the blind person is 29.63% of the total number of persons with disabilities. It can be concluded that people with visual impairment are the highest in persons with disabilities in Indonesia. Therefore the development of Indonesian dictionary for the blind is considered important in this era.Android is a Linux-based operating system that can be used for smart phones and tablet computers. The selection of Android as the Indonesian dictionary base for the visually impaired on the Android platforms is provided platfro open for developers to create applications. In addition to Android also features Talk Back and speech to text that was created specifically for the visually impaired. The feature works as an Android screen reader so that the blind people can enjoy the screen display with sound output. In line with these things Android is considered easier operation and maintenance because it is more practical than conventional dictionary.